ADRM1‐amplified metastasis gene in gastric cancer. Issue 8 (6th June 2015) - Fejzo, Marlena S.; Anderson, Lee; Chen, Hsiao‐Wang; Anghel, Adrian; Zhuo, Jiaying; Anchoori, Ravi; Roden, Richard; Slamon, Dennis J.
<x xml:space="preserve">Abstract</x> The proteasome ubiquitin receptor ADRM1 has been shown to be a driver for 20q13.3 amplification in epithelial cancers including ovarian and colon cancer. We performed array‐CGH on 16 gastric cancer cell lines and found 20q13.3 to be amplified in 19% with the minimal amplified region in gastric cancer cell line AGS spanning a 1 Mb region including ADRM1. Expression microarray analysis shows overexpression of only two genes in the minimal region, ADRM1 and OSBPL2. While RNAi knockdown of both ADRM1 and OSBPL2 led to a slight reduction in growth, only ADRM1 RNAi knockdown led to a significant reduction in migration and growth in soft‐agar. Treatment of AGS cells with the ADRM1 inhibitor RA190 resulted in proteasome inhibition, but RNAi knockdown of ADRM1 did not. However, RNAi knockdown of ADRM1 led to a significant reduction in specific proteins including MNAT1, HRS, and EGFR. We hypothesize that ADRM1 may act in ADRM1‐amplified gastric cancer to alter protein levels of specific oncogenes resulting in an increase in metastatic potential. Selective inhibition of ADRM1 independent of proteasome inhibition may result in a targeted therapy for ADRM1‐amplified gastric cancer. In vivo models are now warranted to validate these findings. © 2015 Wiley Periodicals, Inc.